MAKNA PENAMAAN SAJIAN RITUAL KABASA DARI PERSPEKTIF GASTROLINGUISTIK - Lindayani, Lilik Rita; Rasiah, Rasiah; Azi, Rahmawati; Sifatu, Wa Ode; syahrun, syahrun; La Sawali, La Sawali (Paradigma: Jurnal Kajian Budaya, 2024)
This article is about Munanese (an ethnic group in Southeast Sulawesi) traditional dish kabasa as a form of referential support to the gastrodiplomacy trend. Kabasa is a part of the haroa ritual that features a range of dishes with various ingredients, which is strongly connected to various aspects of the community such as social position, psychology, and environment. In this study, a combination between linguistics as language science and gastronomy which examines food within its culture is considered effective for investigating the semantics of the naming pattern of kabasa dishes in order to document this unique culinary tradition and introduce new concepts in Indonesian gastronomy, particularly that of Southeast Sulawesi. Using the qualitative descriptive method and macrolinguistic approach, this study shows that kabasa naming pattern consists of three semantic levels. Meanwhile, more comprehensive gastrolinguistic analysis on the data suggests that the meanings of the names can be found based on (1) the food ingredients, which are tied to the region’s geographical features and (2) the semantic convention of kabasa itself, which shows an associative relationship between an object, its name, and environmental aspects as contextual clues.